Characterization of The Main Characters in Me Before You By Jojo Moyes: An Analysis of Structure and Plot Dynamics - Tulus, Tulus (Journal of English Language and Education, 2025)
Characterization of the main characters is an essential element in establishing an emotional connection between the reader and the storyline in a novel. Me Before You by Jojo Moyes presents profound characterization through its two main characters, Louisa Clark and Will Traynor, who have contrasting backgrounds and motivations. This study aims to analyze how the characterization of these two characters contributes to the structure and quality of the novel’s plot. The research employs a qualitative approach with text analysis, encompassing character identification, psychological analysis of characters, and exploration of narrative structure. Data were collected through in-depth reading and note-taking of key elements related to character development and their interaction with the plot. The findings reveal that the characterization of Louisa and Will plays a crucial role in shaping the story’s dynamics. Louisa evolves from an insecure individual into a more independent and courageous person, while Will experiences deep internal conflict regarding control over his life. Will's firm adherence to his decision creates intense emotional tension in the plot, reinforcing the central themes of freedom of choice, sacrifice, and the meaning of life. Additionally, validation through literature review and discussions with academics supports the idea that characterization in this novel aligns with concepts in contemporary literature. The study concludes that complex and realistic characterization not only drives the plot but also adds depth to the themes and messages conveyed. Through strong character depiction, Me Before You successfully engages readers emotionally and offers a profound reflection on life choices and their consequences in human existence.